THE FORMATION OF COLUMNAR FIBER TEXTURE IN WOLLASTONITE RIMS BY INDUCED STRESS AND IMPLICATIONS FOR DIFFUSION-CONTROLLED CORONA GROWTH - Milke R.; Wirth R. (My University, 2003)
The evolution of columnar fiber texture was studied in wollastonite reaction rims synthesized by the reaction calcite + quartz=wollastonite + CO2. Experiments were performed at 850 to 950 °C at 100 MPa in dry CO2 and were evaluated by scanning and transmission electron microscopy. Rim growth rates are interpreted as controlled by the diffusion of the SiO2 component through the rims from the quartz–wollastonite to the wollastonite–calcite interface. The temperature dependence of rim growth rates yields an apparent activation energy of 314 ± 53 kJ mol−1. The columnar fibrous wollastonite crystallizes at the quartz–wollastonite interface and comprises the largest parts of the rims. Ultimately, at the growth front strain contrast centers are present in the quartz. The strained volume extends about 200 nm into the quartz grains. We suggest that this might signify deformation of the quartz lattice due to wollastonite crystallization. Wollastonite fiber thickness was measured from TEM images along traverses that represent intermediate positions of the growth front during the experiments. The average thickness is in the 100–200 nm range. Fiber thickness increases with increasing growth temperature. At a given temperature, the thickness of the fibers at the growth front slightly decreases with time, i.e., the number of fiber tips per unit area in the growth front increases. The decrease of the fiber thickness is well fitted by a parabolic rate law. The generation of the columnar fiber texture is interpreted as an effect of induced stresses at the growth front, resulting from the volume increase due to the local reaction. This volume increase forces SiO2 to diffuse along the growth front to the grain boundaries between the wollastonite fibers. These serve as fast diffusion pathways through the rims. The fiber thickness monitors the diffusion distances in the growth front and thus the height of the induced stress gradients. Since interface reactions are usually associated with volume changes, growth rates of reaction rims and zones in coronas are not only controlled by the diffusive mobility of the components but also by the volume restraints on the interface reactions.
Keywords: wollastonite